Comparing the Psychometric Properties of Two Japanese-Translated Scales of the Free Will and Determinism-Plus Scale - Goto, Takayuki (Frontiers in Psychology, 2021)
The free will and determinism-plus scale (FAD-Plus) is one of the most widely used scales to assess people’s lay belief about the existence of free will and deterministic world views. Past research has translated FAD-Plus into various languages for non-English speaking populations, and there exist two Japanese translations of FAD-Plus: the FAD+ and the FAD-J. This study aimed to compare the psychometric properties of FAD+ and FAD-J. Results revealed that while both FAD+ and FAD-J consist of the same four subscales as the original FAD-Plus, some differences exist in the item-level psychometric characteristics. In general, as for the construct validity, although results supported that both scales can assess almost the same construct in terms of the functionalities, FAD-J tends to be slightly more likely to replicate the correlations obtained in the previous research.